2022
DOI: 10.1145/3569483
|View full text |Cite
|
Sign up to set email alerts
|

Generalization and Personalization of Mobile Sensing-Based Mood Inference Models

Abstract: Mood inference with mobile sensing data has been studied in ubicomp literature over the last decade. This inference enables context-aware and personalized user experiences in general mobile apps and valuable feedback and interventions in mobile health apps. However, even though model generalization issues have been highlighted in many studies, the focus has always been on improving the accuracies of models using different sensing modalities and machine learning techniques, with datasets collected in homogeneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Model performance was assessed by performing 5-fold cross-validation, partitioning on subjects, and predictions across folds were concatenated to calculate model performance. Similar to prior work 4 , 6 , within each cross-validation split, models were trained using data collected from 80% of the participants (520 participants), and the trained model was applied to predict CSD in the remaining 20% (130 participants). To analyze performance variability due to specific cross-validation splits, we performed 100 cross-validation trials, shuffling participants into different folds during each trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model performance was assessed by performing 5-fold cross-validation, partitioning on subjects, and predictions across folds were concatenated to calculate model performance. Similar to prior work 4 , 6 , within each cross-validation split, models were trained using data collected from 80% of the participants (520 participants), and the trained model was applied to predict CSD in the remaining 20% (130 participants). To analyze performance variability due to specific cross-validation splits, we performed 100 cross-validation trials, shuffling participants into different folds during each trial.…”
Section: Resultsmentioning
confidence: 99%
“…Initial work showed that depression risk could be predicted from sensed-behavioral data at a similar accuracy to general practitioners 10 in small populations 5 , 11 . More recent work shows that these AI tools predict depression risk at an accuracy only slightly better than a coin flip in larger, more diverse samples 4 , 6 , 12 , 13 . This prior work has not specifically explored why accuracy is reduced in larger samples, and it is unclear how to improve AI tools for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…3.1.1 Feature Design. We design a set of five passive sensing feature categories [59,87,89] to capture smartphone overuse behavior: (a) Phone and App Usage. Understanding smartphone overuse requires a thorough analysis of usage patterns.…”
Section: Machine Learning For Smartphone Overuse Predictionmentioning
confidence: 99%
“…Second, it is elementary that those who collect the data be involved in the research, analysis, and publication. Therefore, in our case, all project partners went to great lengths to ensure that joint research was conducted with the collected data, resulting in joint publications (Schelenz et al, 2021;Meegahapola et al, 2021Meegahapola et al, , 2022Assi et al, 2023). This ensures that all stakeholders benefit from the data they help produce and that the data are used in ways that are relevant to different local contexts.…”
Section: Confronting the Two Sides Of The Neocolonial Circle: Extract...mentioning
confidence: 99%